First-line imatinib in elderly patients with chronic myeloid leukaemia from the CAMELIA registry: Age and dose still matter. (June 2019) - Belohlavkova, Petra; Steinerova, Katerina; Karas, Michal; Skoumalova, Iva; Rohon, Peter; Indrak, Karel; Voglova, Jaroslava; Vrbacky, Filip; Cmunt, Eduard; Necasova, Tereza; Kristkova, Zlatuse; Trneny, Marek; et al.
Highlights: Tyrosine kinase inhibitors have changed the natural course of CML. In the era of TKI age is losing its negative prognostic importance. The responses of the elderly were comparable with those of the younger ones. Abstract: We retrospectively evaluated the role of age and dosage in 372 CML patients (170 women, 202 men) treated with first-line imatinib (IMA) from the records of the CAMELIA registry. The median follow-up of the patients was 82.3 (18.0–177.3) months. The treatment results of 80 elderly patients aged over 65 years at diagnosis were compared in analysis "A" with those of 292 younger patients and in analysis "B" with those of 90 patients younger than 40 and 202 patients aged 40–64. The elderly patients had statistically adverse values of the Sokal, ELTS, and ECOG scores and Charlson comorbidity index in both analyses (p from = 0.012 to ≤ 0.001). Despite a more frequent use of a daily dose lower than 400 mg – in 31 elderly patients (38.8%) than in 45 younger ones (15.4%) (p < 0.001), there were no statistically significant differences in the achievement of optimal haematological, cytogenetic, and molecular responses according to the ELN criteria in both the analyses, A and B. The comparisons of overall survival with CML-related death (OSCML ) and event-free survival (EFS) were insignificant inanalysis A (p = 0.07 and 0.396, respectively) but progression-free survival (PFS) differed significantly (p = 0.007). In analysis B OSCML and PFS differed significantly (p = 0.027 and 0.003) but EFS was similar (p = 0.351). Elderly patients with a sustained dose of IMA of 400 mg/day have insignificantly better OS, PFS, and EFS compared to patients treated with a lower dosage of IMA. The results in the treatment of the elderly CML patients were comparable with those of the younger ones in terms of the probabilities of the achievement of optimal ELN responses. However, the results for the survival probabilities were influenced by age and the IMA dosage.